Study The Various Failure Cases of The Reinforced Concrete Silos: A Literature Review (Texas Journal of Engineering and Technology, 2023)
Silos are unique structures that are put under a wide variety of abnormal loading conditions, which causes them to fail in unusual ways. The failure of a reinforced concrete silo can have highly destructive or damaging effects because it is possible for this to result in the misplacement of the utensil, the pollution of the substance that it houses, the absence of the substance itself, the need for cleanup, the costs associated with replacing the container, damage to the environment, and even the possibility of a person's death. This study offers a comprehensive overview and discussion of the everyday or extraordinary reinforced concrete silo failures because of the risk of explosion and bursting, the creation of asymmetrical loads while filling or discharging, as well as excessive and nonuniform soil pressure, the degradation of concrete silos brought on by silage acids, the collapse of the internal structure, and thermal ratcheting. These failures occurred for a variety of reasons, such as blowing up or rupturing; weights that are not evenly distributed when being filled or emptied; large and nonuniform damage to silos and failures as a result of multiple earthquakes are also presented here. Errors in construction, usage, and design have been identified as the primary reasons for the failure of silos.